Exploring The History of Islam in Java Through The Wayang Tengul Art of Bojonegoro - Khamid, Abdul; Setiawan, Nanang; Huda, Muhammad Miftakhul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
This research aims to preserve the local culture of the Indonesian people and can be a learning medium to introduce the history of the development of Islam to the nation's generations. Moreover, currently many opinions are emerging regarding the prohibition of using wayang, even though the Wali Songo in spreading Islam in Indonesia also uses the medium of wayang. This research is qualitative, involving in-depth interviews with Wayang characters as well as continuous observation and analysis with the aim of obtaining valid data. The results of the research reveal that Wayang Tengul can be a medium for introducing the history of the development of Islam in Indonesia and plays an important role in establishing and maintaining religious moderation among the people of Bojonegoro Regency. It is hoped that this research can increase knowledge literacy about local culture and develop insight into religious moderation in Indonesia.